Synthesis and Characterization of Organotin(IV) Complexes Derivatives of Methyl- and Nitro- Substituted Monocarboxylic Acid: Preliminary in vitro Antibacterial Screening Activity - Win, Yip-Foo; Choong, Chen-Shang; Ha, Sie-Tiong; Teoh, Siang-Guan; Eltaher Eltayeb, Naser (Asian Journal of Chemistry, 2012)
Organotin(IV) carboxylate complexes derivatives of 3-methyl-4-nitrobenzoic acid (3-CH3-4-NO2-C6H3COOH) and 4-methyl-3-nitrobenzoic acid (4-CH3-3-NO2-C6H3COOH) have been successfully synthesized. Two dibutyltin(IV) complexes with the general formulae [X-CH3-Y-NO2-C6H3COO(C4H9)2Sn]2O2 (X = meta, Y = para 1; X = para, Y = meta 3) and another two triphenyltin(IV) complexes with the general formulae X-CH3-Y-NO2-C6H3COO(C6H5)3Sn·CH3OH (X = meta, Y = para 2; X = para, Y = meta 4) were successfully synthesized. The acids and complexes 1-4 obtained were characterized quantitatively and qualitatively. Results of the infrared and NMR spectroscopy on the acids and complexes showed that the coordination took place via oxygen atoms from the carboxylate anions. Based on the spectroscopy studies indicated that one methanol molecule also take part in the coordination to tin(IV) atoms moiety in complexes 2 and 4 resulting the tin(IV) atoms exhibited five coordination. From the preliminary in vitro antibacterial screening activity, triphenyltin(IV) complexes (2 and 4) showed better activity compared to diorganotin(IV) complexes (1 and 3).